Studies on the Natural Resistance of Timbers to Termite Attack. VI. Laboratory Evaluation of the Resistance of ’Mundani’, ’Anjan’ and ’Banati’ to Microcerotermes beesoni Snyder (Insecta : Isoptera Amitermitinae) - Sen-sarma, P. K.; Mishra, S. C.; Gupta, B. K. (Indian Forester, 1970)
Heartwood of ’mundani’ (Actocarpus fraxinifolius Wight), anjan (Hardwickia binata Roxb.) and ’banati’ (Lophopetalum wightianum Arn.) were tested in laoratory under controlled condition of temperature (28Â° + 1Â°C) and relative humidity (85-90% r.h.) using laboratory colonies of Microcerotermes beesoni Snyder which builds wood-carton nests in the North India. Each test colony comprised of ca 1000 workers which were measured volumetrically and tested for 60 days. The results show that the heartwood of ’anjan’ and wood of ’banati’ are very resistant to attack by termites (mean % weight-loss: outer heartwood 0.075 and inner heartwood 2.61 in case of ’anjan’ and outer region 0.014 and inner region 0.68 in case of ’banati’). Heartwood of ’mundani, however, proved susceptible to termite attack (mean % weight-loss: outer heartwood 33.95, inner heartwood 54.33).